Drug flibanserin-in hypoactive sexual desire disorder - Pugazhenthan Thangaraju; Hemasri Velmurugan; Sree Sudha TY (BMJ Publishing Group, 2022)
Hypoactive sexual desire disorder (HSDD) is a widely known type of female sexual dysfunction that could also cause emotional distress and relationship problems. Flibanserin, a benzimidazole, was being studied as a treatment for premenopausal women with hypoactive sexual desire disorder because there was no accurate drug therapy available at the time (HSDD). The US Food and Drug Administration (FDA) approved Flibanserin in 2015 for the treatment of generalised acquired HSDD in premenopausal women. It has a high affinity for postsynaptic 5-HT-1A receptors (agonist) and 5-HT-2A receptors (antagonist), and it tends to work by increasing dopamine and noradrenaline levels in the brain while decreasing serotonin levels. This review was to assess Flibanserin efficacy and safety and it is found the drug Flibanserin benefits did not outweigh the risks in premenopausal and postmenopausal women.